Implementation of Critical Thinking Values in Grade IV Indonesian Language Textbooks of The Merdeka Curriculum : A Content Analysis in The Application of The Pancasila Student Profile - Sadiah, Enok; Yanti, Prima Gusti; Tarmini, Wini (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to elaborate on the implementation of critical thinking values in several textbooks used in Indonesia as an essential aspect of the Pancasila Student Profile. The research approach utilized a qualitative content analysis method to examine elements of critical thinking in four Grade IV Indonesian Language textbooks within the Merdeka Curriculum, published by Erlangga, Yudistira, Bumi Aksara, and Kemendikbudristek. The findings showed that Grade IV Indonesian Language textbooks from these four publishers clearly implemented critical thinking characteristics, each with different emphases. Erlangga focuses on